Effect of IL-21 on the Balance of Th17 Cells/Treg Cells in the Pathogenesis of Graves' Disease. (2nd October 2019) - Tan, Yan; Chen, Wei; Liu, Chun; Zheng, Xiaoya; Guo, Ai; Long, Jian
ABSTRACT: Graves' disease (GD) is a common organ-specific autoimmune disease, and its pathogenesis is still unclear. The aim of this study is to investigate the role of interleukin (IL)-21 in the regulation of Th17/Treg cells in GD. We recruited 28 newly diagnosed GD patients, 27 GD patients in remission (eGD), and 24 normal controls (NC). Thyroid function and autoantibodies were evaluated by electrochemical luminescence. Peripheral blood mononuclear cells (PBMCs) were isolated and cultured with or without recombinant human interleukin-21 (rhIL-21), and mRNA and protein levels were quantified by real-time PCR and ELISA, respectively. Compared with those in the eGD and control groups, the thyroid function indexes and autoantibodies levels were significantly different in the GD group ( P < 0.05). Without rhIL-21 stimulation, the expression levels of retinoid-related orphan gamma t (RORγt), IL-17, IL-22, forkhead box protein P3 (Foxp3) and IL-10 mRNA and the IL-10 and IL-22 proteins were significantly higher in the GD group than those in the eGD and control groups ( P < 0.05). rhIL-21 stimulation increased the RORγt, IL-17, and IL-22 mRNA levels and IL-22 protein levels and decreased the Foxp3 and IL-10 mRNA levels and IL-10 protein levels ( P < 0.05) in the GD group. In conclusion, our analyses demonstrated that IL-21 might induce the differentiation of CD4 + T cells to Th17 cells and reduce Treg cell differentiation, which could contribute to activation of the downstream immune response and the pathogenesis of GD.